Fuzzy AHP approach for risk assessment in manganese mines of India. (2017) - Verma, Shikha; Chaudhari, Sharad
Mining has always been a dangerous occupation. Operations performed in ore extraction and processing are highly risky in nature. The presence of potential hazards associated with a considerable level of risk, leading to injuries and fatalities makes workplace and personnel safety an issue of concern for this sector. This industry has shown considerable growth in the past few decades, to maintain the upward trend in its growth; safe working environment has become a dire necessity. In the present article, fuzzy analytical hierarchy process (FAHP) for risk assessment is presented. The aim of this work is to identify potential hazards in mining sites, and prioritise them based upon evidences of their risky behaviour. This work presents the database for health and safety hazards and their ranking based upon the identified risk priorities in underground and opencast manganese mines in Madhya Pradesh and Maharashtra regions of India. The outcome of the proposed approach is hazard priorities which can aid safety analysts to understand the precedence of severity associated with the hazards so that accordingly mitigation plans to treat them can be formulated. This can enhance the level of preparedness in this industry against any sudden and unfavourable event like accidents.